A comparative evaluation of metallurgical properties of stainless steel and TMA archwires with timolium and titanium niobium archwires - An in vitro study - Vijayalakshmi R; Nagachandran K; Kummi Pradeep; Jayakumar P (Wolters Kluwer Medknow Publications, 2009)
Objectives: This study aims to evaluate and compare the mechanical and metallurgical properties of stainless steel and titanium molybdenum alloy (TMA) archwires, with recently introduced timolium and titanium niobium arch wires. Materials and Methods: Archwires were categorized into four groups (group I to IV) with 10 samples in each group. They were evaluated for tensile strength, yield strength, modulus of elasticity, load deflection, frictional properties and weld characteristics. Results: The results were statistically analyzed using ANOVA test and it indicated that stainless steel has high strength, high stiffness and low friction compared to other arch wires, thereby proving that it is the best choice for both sliding as well as frictionless retraction mechanics. TMA with its high formability, low stiffness and low load deflection property is suited to apply consistent force in malaligned teeth but, high friction limits its use in retraction only with loop mechanics. Conclusion: Timolium possesses comparatively low stiffness, better strength and behaves as an intermediate between stainless steel and TMA and hence can be tried for almost all clinical situations. Low springback and high formability of titanium-niobium archwire allows creation of finishing bends and thus it can be used as finishing archwire.